Les élections provinciales dans le Québec - Hamelin, Jean; Letarte, Jacques; Hamelin, Marcel (Cahiers de géographie du Québec, 1959)
This essay on electoral geography, the first, perhaps, to be published in Canada, is divided into four distinct parts. The first one deals with the themes of the twenty five provincial electoral campaigns. It includes maps showing the results of the votation in every county of the Province, as divided between the two main political parties, the Liberal and the Conservative. The second part, almost exclusively graphic, examines the political attitude of every provincial county. To circumvent the various problems, graphic curves have been established, indicating the percentage of the liberal and conservative voters and of the nonvoters. In a third part, some aspects of a very particular electoral phenomenon, abstention, are studied. After all possible causes of error had been discarded, a nonvoter curve was obtained, which is used, in particular, to study the fluctuations of the parties. Finally, the influence of the rural vote, a basic element in a long life ministerial party, the geographical distribution of the parties and its evolution within the regions according to certain causes v.g. economic crises, and the Québec electoral System, in relation to the vote and to the parties, are analyzed in a last part about the conditions of political life in the Province of Québec.